Body Awareness, Mindfulness and Affect: Does the Kind of Physical Activity Make a Difference? - Tihanyi, Benedek T.; Sági, Andrea; Csala, Barbara; Tolnai, Nóra; Köteles, Ferenc (European Journal of Mental Health, 2016)
The aim of this cross-sectional study is to explore expected differences in the connection betweenparticular physical activities and positive and negative affect, body awareness or mindfulness.Additionally, we describe the so-called tingling phenomenon (i.e. skin-related sensations evokedby focusing on a body part) in terms of prevalence, gender differences and psychological concomitants.A total of 1,057 individuals (331 male; mean age: 30.6 ± 10.17 years) practicing yoga,Pilates training, kung fu, aerobic, or ballroom dance completed our questionnaire. Analysingdata of all sports together, weekly frequency of practice, as opposed to time elapsed since startingpractice, was connected to lower levels of negative affect and somatosensory amplification, andto higher levels of positive affect. Advanced yoga and Pilates participants showed higher bodyawareness; advanced kung fu participants amplified bodily signals the least, and aerobic wasrelated to the highest positive affect. Among beginners, there were no practically relevant differencesin the assessed constructs. These results might help to clarify the common and differentpsychological properties that are needed for and/or can be developed by different sports.